How is climate change incorporated into environmental impact assessments (EIAs) in South Africa? - Aljareo, Abdulhakim (My University, 2015)
Climate change is an issue of global significance resulting in trans-boundary environmental and socio-economic impacts. South Africa is involved in the international efforts to address climate change, has accepted the findings of the Intergovernmental Panel on Climate Change (IPCC) Assessment Report and developed a National Climate Change Response Policy, listing the impacts of climate change on the sustainable development in South Africa. The main causes of climate change are Greenhouse Gases (GHGs), which have been emitted from different development activities over temporal and spatial scales. In order to reduce the emissions of GHGs and protect proposed development projects from climate change impacts, climate change mitigation and adaptation measures should be incorporated into Environmental Impact Assessment (EIA). This research aimed to describe climate change incorporation into the EIA legal regime and practice in South Africa, based on climate change impacts on sustainable development and the role of EIA in considering climate change. The methodology involved reviewing EIA regulations and related legislation, EIA case studies from Gauteng province conducted between 2010 and 2013, key informant interviews with Environmental Assessment Practitioners (EAPs), and discussion on the linkedin group of the International Association for Impact Assessment of South Africa (IAIAsa). The study concluded that climate change is not explicitly incorporated into the EIA regime, but it is implied in the EIA regulations and related legislation. Largely as a result of the lack of climate change incorporation in the EIA legal regime, climate change is not adequately considered in the EIA practice. In order to support the contribution of EIA to sustainable development in South Africa, It is recommended that climate change should be incorporated into EIA regulations in the next amendment of NEMA. This can be done through including listed activities that require climate change incorporation into the EIA based on type of an activity and/or specific receiving environments. It is also suggested that EIA guidelines for climate change consideration be developed. Further recommendations include supporting the role that Strategic Environmental Assessment (SEA) and Environmental Management Framework (EMF) play, in conjunction with the EIA, in considering climate change; increasing the availability of accurate, local climate change data and modelling technology; developing staff capacity and awareness about climate change, and building EAP’s ability to incorporate climate change in the EIA through the support of government related authorities and associations such as IAIAsa and EAPSA. Key words: climate change, EIA, mitigation, adaptation, EIA legal regime, EIA practice.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science by Coursework and Research Report. Johannesburg 2014.
Keywords: Climatic changes.; Global temperature changes.; Climatic changes - Environmental aspects.; Envoronmental impact analysis.